Oxidative stress and endoplasmic reticulum (ER) stress in the development of neonatal hypoxic–ischaemic brain injury - Thornton, Claire (Biochem Soc Trans, 2017)
Birth asphyxia in term neonates affects 1–2/1000 live births and results in the development of hypoxic–ischaemic encephalopathy with devastating life-long consequences. The majority of neuronal cell death occurs with a delay, providing the potential of a treatment window within which to act. Currently, treatment options are limited to therapeutic hypothermia which is not universally successful. To identify new interventions, we need to understand the molecular mechanisms underlying the injury. Here, we provide an overview of the contribution of both oxidative stress and endoplasmic reticulum stress in the development of neonatal brain injury and identify current preclinical therapeutic strategies.